Protected Areas of the World: a review of National Systems. Vol 2: Palearctic - United Nations Environment Programme World Conservation Monitoring Centre (United Nations Environment Programme-WCMC) (UNEP World Conservation Monitoring Centre (UNEP-WCMC), 2016)
This book is organised into national (or occasionally sub-national) accounts, each comprising a description of the national protected areas system, accompanied by a summary list and map of protected areas. The book is divided into three volumes, with volume one covering the Indomalayan, Oceanian, Australian and Antarctic realms, volume two the Palearctic and Afrotropical realms, and volume three the Nearctic and Neotropical realms. Publication of such a book serves two purposes. First, it provides extensive background information on the protected area systems of the world, relevant to several plenary sessions and workshops at the IV World Congress on National Parks and Protected Areas. In particular, it is a contribution to the third plenary session The Contributions of Protected Areas to Sustaining Society: A Global Review. Secondly, and perhaps more significantly, it is also part of the process of information collection and verification. Feedback from protected areas professionals, and others familiar with protected areas, is therefore both welcomed and encouraged, because only by a continual process of review and update can we present a true picture.